Waste Analysis in Connection Clamp Production Process with Lean Manufacturing and Failure Mode Effect Analysis - Faishal Hidayatulloh; Rr. Rochmoeljati (Journal La Multiapp, 2026)
UD H and M Electric is a manufacturing company engaged in the production of medium voltage overhead line (SUTM) components, one of its products is the Connection Clamp. The purpose of this study is to determine the level of waste that occurs and provide suggestions for improvements to reduce waste. The research data used is questionnaire data with respondents who meet the qualifications and know the entire flow of the Connection Clamp production process, as well as waste data that occurs during the production process. To determine the level of waste that occurs and provide suggestions for improvements, the Waste Assessment Model, Process Activity Mapping, Fishone Diagram, and Failure Mode and Effect Analysis methods are used. In the Waste Assessment Model method, the top three critical levels of waste were obtained, namely waste defect of 19.55%, waste motion of 16.88%, waste transportation of 16.10%. In the Failure Mode and Effect Analysis, the Risk Priority Number (RPN) value was obtained from the top three wastes with each sub-waste, namely waste motion sub-waste lifting products manually with a score of 280, waste motion sub-waste rearranging before the process with a score of 240, waste transport, namely the distance of the work station is less than optimal with a score of 200, waste reject sub-waste cracked plates with a score of 168, waste Defect, namely imperfect layers with a score of 168.